Pengembangan Studi Agama-Agama Dalam Konteks Mayoritas Muslim (Sebuah Tawaran) - Faisal, Faisal; Rusli, Ayu Rustriana (Al-Adyan: Journal of Religious Studies, 2023)
This article aims to offer the development of SAA studies, especially at UIN Imam Bonjol Padang in the context of the Muslim majority. Overlapping course materials and difficulties in syllabus development have an impact on the unclear scientific direction of the study program. Including the lack of attention to the dynamics of Islam in West Sumatra. For this reason, it is necessary to formulate the characteristics of the study program that color the development of studies by adapting the pattern of similar study programs at UIN Jakarta and Yogyakarta. This field research uses qualitative methods, with data collection tools of observation, interviews, and documentation. This research borrows the grand theory of constructivism, especially Karl Mannheim's sociology of knowledge, which sees the strong socio-cultural and historical influence on knowledge. The results found that the pattern of development of SAA studies at UIN Jakarta is built on its distinctive characteristics as an institution whose existence in the metropolitan capital city so that its studies are more theoretically conceptual and responsive to actual issues. Then the pattern of UIN Yogyakarta is built on the distinctive characteristics of integration-interconnection of Islamic science and multicultural Indonesia. While the relevant pattern of SAA UIN Padang is to carry "majority Islam" as a distinctive characteristic. This is linear with the fact of its existence in the midst of West Sumatra society with the dominance of Minangkabau ethnicity which makes Islam a socio-cultural foundation. It is on this distinctive characteristic that the pattern of study development is constructed. Artikel ini bertujuan memberikan penawaran terhadap pengembangan kajian SAA khususnya di UIN Imam Bonjol Padang dalam konteks mayoritas muslim. Tumpang tindih materi kuliah serta kesulitan pengembangan silabus berdampak pada ketidakjelasan arah keilmuan program studi. Termasuk kurangnya perhatian terhadap dinamika Islam di Sumatera Barat. Untuk itu perlu dirumuskan penciri khas prodi yang mewarnai pengembangan kajian dengan mengadaptasi pola prodi serupa di UIN Jakarta dan Yogyakarta. Riset lapangan ini menggunakan metode kualitatif, dengan alat pengumpul data observasi, wawancara, dan dokumentasi. Riset ini meminjam grand theory konstruktivisme khususnya sosiologi pengetahuannya Karl Mannheim yang melihat pengaruh kuat sosial-budaya dan historis terhadap pengetahuan. Hasil riset menemukan bahwa pola pengembangan kajian SAA di UIN Jakarta dibangun di atas penciri khasnya sebagai institusi yang eksistensinya di ibu kota metropolitan sehingga kajiannya lebih teoretis konseptual dan responsif terhadap isu-isu aktual. Kemudian pola UIN Yogyakarta dibangun di atas penciri khas integrasi-interkoneksi ilmu keislaman dan keindonesiaan yang multikultural. Sementara pola SAA UIN Padang yang relevan adalah mengusung “Islam mayoritas” sebagai penciri khas. Ini linear dengan fakta eksistensinya di tengah masyarakat Sumatera Barat dengan dominasi etnis Minangkabau yang menjadikan Islam sebagai landasan sosio-kultural. Di atas penciri khas inilah pola pengembangan kajian dikonstruk.